Single-Cell Approach to Influenza-Specific CD8+ T Cell Receptor Repertoires Across Different Age Groups, Tissues, and Following Influenza Virus Infection - Sant, Sneha; Grzelak, Ludivine; Wang, Zhongfang; Pizzolla, Angela; Koutsakos, Marios; Crowe, Jane; Loudovaris, Thomas; Mannering, Stuart I.; Westall, Glen P.; Wakim, Linda M.; Rossjohn, Jamie; Gras, Stephanie; et al. (Frontiers in Immunology, 2018)
CD8+ T cells recognizing antigenic peptides derived from conserved internal viral proteins confer broad protection against distinct influenza viruses. As memory CD8+ T cells change throughout the human lifetime and across tissue compartments, we investigated how T cell receptor (TCR) composition and diversity relate to memory CD8+ T cells across anatomically-different sites and immunologically-distinct phases of human life. We used ex vivo peptide-HLA tetramer magnetic enrichment, single-cell multiplex RT-PCR for both the TCR-alpha (TCR ) and TCR-beta (TCR ) chains, and newly-established TCRdist and GLIPH (Grouping of Lymphocyte Interactions by Paratope Hotspots) algorithms to compare TCRs directed against the most prominent human influenza epitope, HLA-A*02:01-M158-66 (A2+M158). We dissected memory TCR repertoires directed towards A2+M158 CD8+ T cells within human tissues and compared them to human peripheral blood of young and elderly adults. Furthermore, we compared these memory CD8+ T cell repertoires to A2+M158 CD8+ TCRs during acute influenza disease in patients hospitalized with avian A/H7N9 virus. Our study provides the first ex vivo comparative analysis of paired antigen-specific TCR-alpha/beta clonotypes across different tissues and peripheral blood across different age groups. We show that human A2+M158 CD8+ T cells can be readily detected in human lungs, spleens and lymph nodes, and that tissue A2+M158 TCR repertoires reflect A2+M158 TCR clonotypes derived from peripheral blood in healthy adults and influenza-infected patients. A2+M158 TCR repertoires displayed distinct features only in elderly adults, with largely-expanded private TCR clonotypes replacing the prominent and public TRBV19/TRAV27 TCRs. Our study provides novel findings on influenza-specific TCR repertoires within human tissues, raises the question of how we can prevent the loss of optimal TCR signatures with aging and provides important insights into the rational design of T cell-mediated vaccines and immunotherapies.